Increasing the energy efficiency of power supply systems for solar greenhouses with autonomous energy complex (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This paper presents the results of experimental research. Two solar greenhouses with a total area of 200 square meters were constructed at the National Research Institute of Renewable Energy under the Ministry of Energy of the Republic of Uzbekistan. Each solar greenhouse has an area of 100 square meters. Two biogas plants, each with a capacity of 3 tons, were built to supply heat to the greenhouses. A photovoltaic station with energy storage with a nominal capacity of 5 kW was installed to supply electricity. The research results show that the output indicators of the biogas plant and the autonomous photovoltaic station with a nominal capacity of 5 kW are sufficient to ensure uninterrupted and efficient autonomous power supply to the greenhouse, including for consumers in mountainous and rural regions remote from the general distribution grid.
Keywords: solar energy, solar greenhouse, photovoltaic station, biogas plant, thermal energy, biogas, efficiency